Intensifikasi Program Pembinaan Sebagai Upaya Peningkatan Mutu Guru di Lembaga Kursus Al-Qur'an Masjid Al-Falah Surabaya - Ahmad Junaidi (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2019)
In the process of formal, non-formal and informal education, a teacher is a determining factor for his students success. Therefore, sufficient competence, skills in a variety of representative fields as well as quality-scientific specialization are essential capital that must be continuously improved in order to realize quality- education services for all students. So, all Educational Institutions including the Al-quran Course of Al-falah Mosque Institute are responsible for facilitating teachers developing to achieve their best quality by conducting intensive coaching as mandated by Government Regulation No. 19 of 2005. This research was conducted by using a descriptive qualitative approach, that the aim is knowing generally the quality of teachers, the variety and the realization of intensive coaching programmed twice every month with the conclusion that teachers coaching at the Alquran -Course Institute of Al-falah Mosque (LKF) is carried out continuously with high intensity and significant results.